Identifikasi Bakteri Escherichia Coli Pada Es Kristal Di Rumah Makan Kecamatan Baiturrahman - Banda Aceh - Yuni Dewi Safrida; Thaharah Thaharah (Fakultas Teknik, 2020)
Water is the main component for producing crystal ice cubes, where the water used should fulfill the drinking water criteria that was not allowed to contain Escherichia coli. This research was conducted at the Microbiology Laboratory, AKAFARMA, Banda Aceh. This study aimed to determine the presence of contamination of Escherichia coli bacteria contained in crystal ice cubes. This research used a descriptive method. The results showed that the six samples of crystal ice cubes in the Baiturrahman District restaurant negatively contained Escherichia coli because they did not show colors that match the characteristics of Escherichia coli bacteria.